Elasticity reducing agent for low-carbon high-compactness sprayed concrete as well as preparation method and application of elasticity reducing agent

By using low-carbon high-density elastic reductant in sprayed concrete, combining rheology and viscosity-enhancing components, the problems of high rebound rate and low strength of sprayed concrete are solved, and the rebound rate and density and strength are reduced. effect.

CN119241127AActive Publication Date: 2025-01-03CCCC SECOND HARBOR ENGINEERING CO LTD

Patent Information

Application Number
CN202411332203.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The poor conjugation of existing sprayed concrete leads to a high rebound rate, and traditional tackifiers have limited effect in reducing rebound rate, and may lead to a decrease in concrete strength.

Method used

Use low-carbon and high-density spraying concrete to spray elastic agents, including rheological components, viscosity-enhancing components and early strength components, and pass manganese slag powder, silicon fume, tailings powder loaded with nanomodified cellulose ether, etc. Components to improve the viscosity and density of concrete and reduce the rebound rate.

Benefits of technology

Effectively reduce the rebound rate of sprayed concrete, improve the density and strength of concrete, and achieve the effect of low carbon, low rebound, high density, and improve the yield stress and plastic viscosity of sprayed concrete, reduce harmful porosity, and improve pressure resistance. strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005057290220000091
    Figure BDA0005057290220000091
  • Figure BDA0005057290220000093
    Figure BDA0005057290220000093
  • Figure BDA0005057290220000101
    Figure BDA0005057290220000101
Patent Text Reader

Abstract

The invention discloses a low-carbon high-compactness shotcrete elasticity reducing agent and a preparation method and application thereof, and relates to the field of building material concrete admixtures, the elasticity reducing agent comprises the following components by mass: 53-73% of a rheological component, 15-25% of a tackifying component, 10-18% of an early strength component, and 0.5-4% of a setting adjusting component; the rheological component comprises manganese slag powder and silica fume, and the tackifying component is tailing powder loaded with nano modified cellulose ether. The viscosity of sprayed concrete is increased through the tackifying component, the slurry wrapping property of the concrete is improved, the yield stress of the concrete is improved through the rheological component, and the early strength component is combined to synergistically improve the wall-adhering and quick-hardening properties after the material is sprayed, so that the rebound rate is reduced; the nano-particles loaded on the organic matter are hydrated in pores, harmful pores are directionally filled, the compactness and strength of the sprayed concrete are effectively improved, and low-carbon, low-resilience and high-compactness of the sprayed concrete are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building material concrete admixtures, and in particular to a resilient reducing agent for low-carbon high-density shotcrete and a preparation method thereof. Background Art

[0002] Shotcrete refers to a special type of concrete that uses a spraying machine and compressed air to spray concrete onto the sprayed surface at high speed, quickly solidifying and generating strength. Compared with cast-in-place concrete, machine spraying construction has the advantages of short solidification time, convenient construction, shortened construction period, and cost savings. It is widely used in spray reinforcement for coal mine shafts, tunnels, culverts and other projects. However, when using shotcrete in tunnel projects, due to the poor cohesion of shotcrete and the relatively smooth tunnel wall, the bonding force between the shotcrete and the wall becomes smaller, resulting in a large rebound rate, resulting in a low pass rate for shotcrete.

[0003] Adding thickeners to concrete can improve the cohesiveness of the material and reduce the rebound rate. Existing thickeners are of two types: inorganic and organic. Inorganic thickeners are mainly used to reduce the thickness of the water film layer, increase the interaction resistance between particles, and improve the slurry wrapping. They have no obvious improvement effect on the bonding viscosity between particles and aggregates, and have limited effect on reducing the rebound of shotcrete. Organic thickeners are branched hydrophilic macromolecular organic substances with good adhesion to particles. At the same time, they achieve the purpose of viscosity and thickening through water adsorption and aggregation and long chain entanglement. The water gathered by the macromolecular chain will cause the pores to become larger and form harmful pores after hydration or evaporation, resulting in an increase in the porosity of the concrete and a significant decrease in strength. At present, traditional thickening materials have obvious defects in reducing the rebound of shotcrete.

[0004] Therefore, it is necessary to develop a rebound reducing agent that can reduce the rebound of shotcrete and improve the density and strength of concrete. Summary of the invention

[0005] The purpose of the present invention is to solve the above-mentioned shortcomings of the background technology and provide a rebound reducing agent that can reduce the rebound of shotcrete and improve the density and strength of concrete.

[0006] The technical solution of the present invention is: a low-carbon high-density shotcrete elasticity reducing agent, comprising the following components in percentage by mass:

[0007] Rheological component 53-73%, viscosity increasing component 15-25%, early strength component 10-18%, setting regulating component 0.5-4%, the sum of the mass percentages of the above components is 100%;

[0008] The rheological components include manganese slag powder and silica fume, the viscosity-increasing component is tailings powder loaded with nano-modified cellulose ether, the early strength component includes one or more of calcium formate, sodium sulfate, polyaluminum sulfate, lithium sulfate, aluminate cement, and sulphoaluminate cement, and the setting regulating component is one or more of sodium gluconate, sodium tripolyphosphate, boric acid, and citric acid.

[0009] Preferably, in the rheological component, the mass ratio of manganese slag powder to silicon ash is 1.5-3.0:1, and the specific surface area of ​​manganese slag powder is 600-800m 2 / kg, the specific surface area of ​​the silica ash is 15000-20000m 2 / kg.

[0010] The specific surface area of ​​manganese slag powder in the above scheme is 600-800m 2 / kg, the purpose is that the manganese slag powder particles have a large specific surface area and an uneven surface, which can reduce the thickness of the water film layer on the particle surface and increase the relative resistance to movement between particles, thereby increasing the fluid yield stress and improving the wall hanging performance of the concrete slurry.

[0011] The specific surface area of ​​silica fume in the above scheme is 15000-20000m 2 / kg, the purpose is to fill the gaps between cement particles with fine silica fume to make the paste denser. In addition, silica fume has a larger specific surface area and a larger water requirement. Due to the reaction of volcanic ash and the reduction of free water, the paste at the interface is dense, the Ca(OH)2 crystals are refined, the transition zone becomes thinner, and the bonding between the paste and the aggregate interface is increased.

[0012] Preferably, the tailings powder loaded with nano-modified cellulose ether is prepared by a method comprising the following steps:

[0013] S1. Prepare calcium nitrate and sodium metasilicate nonahydrate into aqueous solutions to obtain solutions A and B, disperse polyether macromonomer in water to form dispersion C, dissolve nonionic water-soluble cellulose ether in water to form solution D, slowly and synchronously add solutions A and B to dispersion C and stir at a stirring rate of 300-500 rpm, add solution D to dispersion C when half of solutions A and B are added, and stir at a high speed at a stirring rate of 1200-2000 rpm until solutions A and B are synchronously added to obtain a nano-modified cellulose ether solution;

[0014] S2, crushing the tailings sand containing a porous structure into tailings particles with a particle size of 0.5 to 2 mm and a pore size of 100 to 500 nm, wherein the tailings sand is one or more of copper tailings sand and iron tailings sand;

[0015] S3, soaking the tailing particles obtained in step S2 in the nano-modified cellulose ether solution obtained in step S1 for 30 to 60 minutes, drying, cooling, and grinding to a specific surface area of ​​50 to 150 m 2 / g, and the tailings powder loaded with nano-modified cellulose ether was obtained.

[0016] The tailings powder loaded with nano-modified cellulose ether prepared by the above scheme is a multifunctional thickening material with good dispersion, slow release and directional pore filling. The tailings porous particles are used to load the nano-cellulose ether to achieve the effects of slow release and high dispersibility. The high dispersibility can evenly disperse the organic matter into the powder, and the slow release is beneficial to alleviate the concentrated dissolution of the long polymer chains and prevent the local polymer chains from aggregating and forming excessive entanglement. At the same time, the excess nano-CSH crystal nuclei are pre-adsorbed with the cellulose ether molecules, and the nanoparticles will follow the movement of the cellulose ether molecules, nucleate at the place where the cellulose ether molecules wrap water, promote the formation of hydration products, fill the pores after the water is hydrated and evaporated, and prevent the local formation of harmful pores.

[0017] In the above scheme, the functions of each raw material are as follows: calcium nitrate + sodium metasilicate nonahydrate are used to prepare nano CSH crystal nuclei, polyether macromonomers are used to disperse the settled solid particles, cellulose ether is used to provide nano particle loading carriers to bind the nano particles to the cellulose ether molecules, and the tailings porous particles are used to adsorb the nano modified cellulose ether so that it can be better dispersed in the cement paste.

[0018] Furthermore, in step S1, the mass concentration of calcium nitrate in solution A is 20-30%, the mass concentration of sodium metasilicate nonahydrate in aqueous solution is 20-30%, the mass concentration of polyether macromonomer in dispersion C is 5-15%, and the mass concentration of cellulose ether in solution D is 0.1-0.5%;

[0019] Furthermore, in step S1, in step S1, the mass ratio of calcium nitrate: sodium metasilicate nonahydrate: polyether macromonomer: cellulose ether is 100: 100-150: 96-288: 1.2-5.0.

[0020] Furthermore, in step S1, the nonionic water-soluble cellulose ether is one or more of methyl cellulose ether, hydroxypropyl methyl cellulose ether, hydroxymethyl cellulose ether, hydroxyethyl cellulose ether, etc., and has a molecular weight of 20000-100000. Too low a molecular weight will result in poor viscosity enhancement, while too high a molecular weight will cause excessive entanglement of cement particles and reduce the strength of concrete.

[0021] Furthermore, in step S1, the total time of adding solutions A and B is 2 to 4 hours.

[0022] Furthermore, in step S3, the drying temperature is 95-105° C. and the drying time is 3-5 hours.

[0023] The present invention also provides a method for preparing any of the above-mentioned low-carbon and high-density shotcrete elasticity reducing agents, and the rheological component, the viscosity-increasing component, the early strength component, and the setting regulating component are mixed to obtain the low-carbon and high-density shotcrete elasticity reducing agent.

[0024] The present invention also provides the use of any of the above-mentioned low-carbon high-density shotcrete elasticity reducing agents, wherein the elasticity reducing agent is added in an amount that replaces 5% to 10% of the cement in the concrete, that is, the elasticity reducing agent is added in an amount that is 5% to 10% of the total mass of the cement.

[0025] The beneficial effects of the present invention are:

[0026] 1. The viscosity of shotcrete is increased by the viscosity-increasing component, the slurry encapsulation of concrete is improved, the yield stress of concrete is increased by the rheological component, and the early strength component is combined to synergistically improve the bonding, wall hanging and rapid hardening properties of the material after spraying, thereby reducing the rebound rate and increasing the thickness of one-time spraying; the nanoparticles loaded on the organic matter are hydrated in the pores and the harmful pores are directionally filled, which effectively improves the density and strength of the shotcrete and realizes low-carbon, low-rebound and high-density shotcrete.

[0027] 2. The elasticity reducing agent adopts cellulose ether with lower molecular weight to reduce the length of the polymer main chain and reduce the pores formed by water adsorption and aggregation. At the same time, the nanocrystalline core will simultaneously induce cement hydration during the evaporation of water around the thickener molecules to form a large amount of CSH gel to fill the structural pores, thereby achieving directional filling of harmful pores, thereby improving the density of the hydration product and eliminating the adverse effects of organic thickening materials on concrete strength.

[0028] 3. The elasticity reducing agent uses porous tailings sand as inorganic material, and utilizes the porous water absorption and water storage functions of the particles to enhance the rheological properties of the elasticity reducing agent, thereby improving the initial pumping efficiency of the concrete and the anti-sagging performance after injection. At the same time, solid waste is recycled to achieve green and low-carbon.

[0029] 4. By loading nano-modified cellulose ether on porous tailings sand, the efficient dispersion of thickener in powder can be achieved. At the same time, the nano-modified cellulose ether in the pores is gradually dissolved and released, reducing the concentration of thickener molecules in the liquid phase and the entanglement of cement particles, which helps to discharge bubbles during concrete mixing and improve the hydration efficiency of cement particles, thereby improving the strength of early concrete.

[0030] 5. The addition of the elasticity reducing agent of the present invention can effectively improve the yield stress and plastic viscosity of shotcrete, the yield stress can reach above 1321.2Pa, and the plastic viscosity can reach above 192.3Pa·s; at the same time, the harmful porosity is reduced to below 2.5%; and the 1d and 28d compressive strengths are improved, the 1d compressive strength of C25 concrete reaches above 20.2MPa, and the 28d compressive strength reaches above 37.8MPa. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The drugs used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods in the art unless otherwise specified.

[0032] Among the rheological components, the specific surface area of ​​manganese slag powder is 600-800m 2 / kg, the specific surface area of ​​the silica ash is 15000-20000m 2 / kg

[0033] Among the viscosity-increasing components, calcium nitrate, sodium metasilicate nonahydrate, polyether macromonomer, and cellulose ether are commercially available products, and the polyether macromonomer is specifically isobutylene polyethylene glycol ether (HPEG) or isopentenyl polyethylene glycol ether (TPEG), which are commercially available products;

[0034] Among the early strength components, calcium formate, sodium sulfate, polyaluminium sulfate, lithium sulfate, aluminate cement and sulphoaluminate cement are commercially available products;

[0035] Among the adjusting and setting components, sodium gluconate, sodium tripolyphosphate, boric acid and citric acid are commercially available products.

[0036] Example 1

[0037] This embodiment provides a low-carbon high-density shotcrete elasticity reducing agent, including 53 parts of rheological components, 25 parts of viscosity-enhancing components, 18 parts of early strength components, and 4 parts of setting adjustment components by weight. The rheological component is obtained by mixing manganese slag powder and silica fume in a mass ratio of 3:1, the viscosity-enhancing component is tailings powder loaded with nano-modified cellulose ether, the early strength component is calcium formate, and the setting adjustment component is sodium tripolyphosphate.

[0038] The steps for preparing the tailings powder loaded with nano-modified cellulose ether in this embodiment are as follows:

[0039] S1. Preparation of nano-modified cellulose ether: Calcium nitrate and sodium metasilicate nonahydrate were dissolved in distilled water to obtain calcium nitrate aqueous solution A with a mass concentration of 20% and sodium metasilicate nonahydrate aqueous solution B with a mass concentration of 30%, a polyether macromonomer (specifically HPEG in this embodiment) was dispersed in water to prepare a dispersion C (mass concentration of 5%), hydroxypropyl methylcellulose ether was dissolved in water to form a solution D (mass concentration of 0.2%), and then 12g of solution A and 12g of solution B were slowly added to 46g of dispersion C by synchronous dropwise addition for 2h (stirred at a low speed of 500rmp for the first 1h), 30g of cellulose ether aqueous solution D was added after 1h of dropwise addition, and then after 1h of high-speed stirring (at a rate of 1500rmp), solutions A and B were synchronously added dropwise to obtain a nano-modified cellulose ether solution. According to the above specific dosages, in this embodiment, the mass ratio of calcium nitrate: sodium metasilicate nonahydrate: polyether macromonomer: cellulose ether is 100:150:96:2.5.

[0040] S2, the porous copper tailings are crushed into particles with a pore size of 100-500nm and a particle size of 0.5-2mm;

[0041] S3, the tailings particles were soaked in the nano-modified cellulose ether solution for 30 minutes, then taken out and dried at 105℃ for 3 hours. After cooling, the particles were ground into powder by ball mill with a specific surface area of ​​50-150m 2 / g, to obtain tailings powder loaded with nano-modified cellulose ether.

[0042] The preparation method of the elasticity reducing agent for low-carbon and high-density shotcrete is as follows: the rheological component, the viscosity increasing component, the early strength component and the setting regulating component are mixed.

[0043] The elasticity reducing agent of Example 1 was added to the concrete by internal mixing (replacing cement) at a mixing amount of 5%.

[0044] Example 2

[0045] This embodiment provides a low-carbon high-density shotcrete elasticity reducing agent, including 72.5 parts of rheological components, 15 parts of viscosity-enhancing components, 12 parts of early strength components, and 0.5 parts of setting adjustment components by weight. The rheological component is obtained by mixing manganese slag powder and silica fume in a mass ratio of 3:1, the viscosity-enhancing component is tailings powder loaded with nano-modified cellulose ether, the early strength component is sodium sulfate, and the setting adjustment component is boric acid.

[0046] The steps for preparing the tailings powder loaded with nano-modified cellulose ether in this embodiment are as follows:

[0047] S1. Preparation of nano-modified cellulose ether: Calcium nitrate and sodium metasilicate nonahydrate were dissolved in distilled water to obtain calcium nitrate aqueous solution A with a mass concentration of 25% and sodium metasilicate nonahydrate aqueous solution B with a mass concentration of 25%, a polyether macromonomer (specifically TPEG in this embodiment) was dispersed in water to prepare a dispersion C (mass concentration of 10%), hydroxypropyl methylcellulose ether was dissolved in water to form a solution D (mass concentration of 0.4%), and then 12 g of solution A and 12 g of solution B were slowly added to 46 g of dispersion C by synchronous dropwise addition for 4 h (stirring at a low speed of 500 rpm for the first 2 h), 30 g of cellulose ether aqueous solution D was added after 2 h of dropwise addition, and then after 2 h of high-speed stirring (at a rate of 1200 rpm), solutions A and B were synchronously added dropwise to obtain a nano-modified cellulose ether solution. According to the above specific dosages, in this embodiment, the mass ratio of calcium nitrate: sodium metasilicate nonahydrate: polyether macromonomer: cellulose ether is 100:100:153:4.0.

[0048] S2 porous iron tailings are crushed into particles with a pore size of 100-500nm and a particle size of 0.5-2mm;

[0049] S3: Soak the tailings particles in the nano-modified cellulose ether solution for 30 minutes, then remove them and dry them at 105℃ for 3 hours. After cooling, the particles are ground into powder by a ball mill with a specific surface area of ​​50-150m 2 / g, to obtain tailings powder loaded with nano-modified cellulose ether.

[0050] The preparation method of the elasticity reducing agent for low-carbon and high-density shotcrete is as follows: the rheological component, the viscosity increasing component, the early strength component and the setting regulating component are mixed.

[0051] The elasticity reducing agent of Example 2 was added to the concrete by internal mixing (replacing cement) at a mixing amount of 5%.

[0052] Example 3

[0053] This embodiment provides a low-carbon high-density shotcrete elasticity reducing agent, including 63 parts of rheological components, 20 parts of viscosity-enhancing components, 15 parts of early strength components, and 2 parts of setting adjustment components by weight. The rheological component is obtained by mixing manganese slag powder and silica fume in a mass ratio of 3:1, the viscosity-enhancing component is tailings powder loaded with nano-modified cellulose ether, the early strength component is polyaluminum sulfate, and the setting adjustment component is citric acid.

[0054] The steps for preparing the tailings powder loaded with nano-modified cellulose ether in this embodiment are as follows:

[0055] S1. Preparation of nano-modified cellulose ether: Calcium nitrate and sodium metasilicate nonahydrate were dissolved in distilled water to obtain calcium nitrate aqueous solution A with a mass concentration of 25% and sodium metasilicate nonahydrate aqueous solution B with a mass concentration of 30%, a polyether macromonomer (specifically TPEG in this embodiment) was dispersed in water to prepare a dispersion C (mass concentration of 15%), hydroxypropyl methylcellulose ether was dissolved in water to form a solution D (mass concentration of 0.5%), and then 12 g of solution A and 12 g of solution B were slowly added to 46 g of dispersion C by synchronous dropwise addition for 3 h (the first 1.5 h was stirred at a low speed of 500 rpm), and 30 g of cellulose ether aqueous solution D was added after 1.5 h of dropwise addition, and then after 1.5 h of high-speed stirring (at a rate of 2000 rpm), a nano-modified cellulose ether solution was obtained. According to the above specific dosages, in this embodiment, the mass ratio of calcium nitrate: sodium metasilicate nonahydrate: polyether macromonomer: cellulose ether is 100:120:230:5.0.

[0056] S2 porous copper tailings are crushed into particles with a pore size of 100-500nm and a particle size of 0.5-2mm;

[0057] S3: Soak the tailings particles in the nano-modified cellulose ether solution for 30 minutes, then remove them and dry them at 105℃ for 3 hours. After cooling, the particles are ground into powder by a ball mill with a specific surface area of ​​50-150m 2 / g, to obtain tailings powder loaded with nano-modified cellulose ether.

[0058] The preparation method of the elasticity reducing agent for low-carbon and high-density shotcrete is as follows: the rheological component, the viscosity increasing component, the early strength component and the setting regulating component are mixed.

[0059] The elasticity reducing agent of Example 4 was added to the concrete by internal mixing (replacing cement) at a mixing amount of 5%.

[0060] Example 4

[0061] The preparation method of the low-carbon high-density shotcrete resiliency reducing agent in this embodiment is the same as that in embodiment 1, except that the amount of the resiliency reducing agent added to the concrete is 10%.

[0062] Performance Testing

[0063] Comparative Example 1 is a benchmark C25 shotcrete.

[0064] Comparative Example 2 follows the ratio of Example 3 (i.e., 63 parts of rheological component, 20 parts of thickening component, 15 parts of early strength component, and 2 parts of setting component), the thickening component is not pre-adsorbed and loaded, and the cellulose ether, nano CSH crystal nucleus early strength agent, and copper tailings powder raw materials are directly mixed in a mass ratio of 1:140:800 to form the thickening component; the nano crystal nucleus early strength agent is the CSH crystal nucleus early strength agent of Jiangsu Aolaite New Materials Co., Ltd.

[0065] Comparative Example 3 is product HT-01 of Wuhan Yuanjin Building Materials Technology Co., Ltd.

[0066] The C25 shotcrete of the embodiments and comparative examples was prepared according to the following Table 1.

[0067] Table 1 C25 shotcrete mix ratio (kg / m 3 )

[0068]

[0069] The embodiments and comparative examples were tested for 90-min time loss, yield stress, plastic viscosity, side wall rebound rate, vault rebound rate, one-shot thickness, 1-d compressive strength, 28-d compressive strength, and harmful porosity. The yield stress and plastic viscosity were measured using the Viskmat eBT2 rheometer V mode, and the harmful porosity was measured using the AutoPore IV 9510 fully automatic mercury intrusion instrument produced by Mack. The rest were tested according to JGJ / T 372-2016 "Technical Specifications for the Application of Shotcrete". The test results are shown in Tables 2 and 3 below.

[0070] Table 2 Performance test results

[0071]

[0072] Table 3 Performance test results

[0073]

[0074] It can be seen from the test results in Table 2 that the different components of the elasticity reducing agents used in Examples 1, 2, and 3 can be compared with Comparative Example 1. The use of the elasticity reducing agent can effectively improve the yield stress and plastic viscosity of the shotcrete, thereby improving the cohesiveness of the shotcrete during pumping and the bonding performance during spraying, thereby reducing the rebound rate, while reducing the harmful porosity, and improving the 1d and 28d compressive strengths; by comparing the test results of Examples 1, 2, and 3, it can be seen that with the increase of the rheological component, the yield stress of the shotcrete is further increased, the rebound rate is further reduced, and the strength at each age is also improved; by comparing the test results of Example 3 with Example 4, it can be seen that as the amount of the elasticity reducing agent exceeds 5%, the performance improvement is not obvious; by comparing the test results of Example 3 with Comparative Example 2, it can be seen that when the rheological component is not pre-adsorbed and dispersed, the harmful pores cannot be filled in a targeted manner, and the effect of improving the strength is limited; by comparing Example 3 with Comparative Example 3, the elasticity reducing agent product of the present invention has great advantages in reducing rebound and improving strength.

[0075] According to the above test results, the present invention successfully formulates a rebound reducing agent that can reduce the rebound rate of shotcrete and improve the density and strength by using the synergistic effect of viscosity-increasing components, rheological components, early strength components and setting regulating components. It can improve the slurry encapsulation and cohesion of concrete, improve the bonding performance of the material after spraying, thereby reducing the rebound rate and increasing the thickness of one spraying; it can directionally fill harmful pores, effectively improve the density and strength of shotcrete, and achieve low-carbon, low-rebound and high-density shotcrete.

Claims

1. A low-carbon and high-density shotcrete elasticity reducing agent, characterized in that: Includes the following components by mass percentage: Rheological component 53-73%, viscosity increasing component 15-25%, early strength component 10-18%, setting regulating component 0.5-4%, the sum of the mass percentages of the above components is 100%; The rheological components include manganese slag powder and silica fume, the viscosity-increasing component is tailings powder loaded with nano-modified cellulose ether, the early strength component includes one or more of calcium formate, sodium sulfate, polyaluminum sulfate, lithium sulfate, aluminate cement, and sulphoaluminate cement, and the setting regulating component is one or more of sodium gluconate, sodium tripolyphosphate, boric acid, and citric acid.

2. The low-carbon high-density shotcrete elasticity reducing agent according to claim 1, characterized in that: In the rheological component, the mass ratio of manganese slag powder to silicon ash is 1.5-3:1, and the specific surface area of ​​manganese slag powder is 600-800m 2 / kg, the specific surface area of ​​the silica ash is 15000-20000m 2 / kg.

3. The low-carbon high-density shotcrete elasticity reducing agent according to claim 1, characterized in that: The tailings powder loaded with nano-modified cellulose ether is prepared by a method comprising the following steps: S1. Prepare calcium nitrate and sodium metasilicate nonahydrate into aqueous solutions to obtain solutions A and B, disperse polyether macromonomer in water to form dispersion C, dissolve nonionic water-soluble cellulose ether in water to form solution D, slowly and synchronously add solutions A and B to dispersion C and stir at a stirring rate of 300-500 rpm, add solution D to dispersion C when half of solutions A and B are added, and stir at a high speed at a stirring rate of 1200-2000 rpm until solutions A and B are synchronously added to obtain a nano-modified cellulose ether solution; S2, crushing the tailings sand containing a porous structure into tailings particles with a particle size of 0.5 to 2 mm and a pore size of 100 to 500 nm, wherein the tailings sand is one or more of copper tailings sand and iron tailings sand; S3, soaking the tailing particles obtained in step S2 in the nano-modified cellulose ether solution obtained in step S1 for 30 to 60 minutes, drying, cooling, and grinding to a specific surface area of ​​50 to 150 m 2 / g, and the tailings powder loaded with nano-modified cellulose ether was obtained.

4. The low-carbon high-density shotcrete elasticity reducing agent according to claim 3, characterized in that: In step S1, the mass concentration of calcium nitrate in solution A is 20-30%, the mass concentration of sodium metasilicate nonahydrate in aqueous solution is 20-30%, the mass concentration of polyether macromonomer in dispersion C is 5-15%, and the mass concentration of cellulose ether in solution D is 0.1-0.5%.

5. The low-carbon high-density shotcrete elasticity reducing agent according to claim 4, characterized in that: In step S1, the mass ratio of calcium nitrate: sodium metasilicate nonahydrate: polyether macromonomer: cellulose ether is 100: 100-150: 96-288: 1.2-5.

0.

6. The low-carbon high-density shotcrete elasticity reducing agent according to claim 3, characterized in that: In step S1, the nonionic water-soluble cellulose ether is one or more of methyl cellulose ether, hydroxypropyl methyl cellulose ether, hydroxymethyl cellulose ether, hydroxyethyl cellulose ether, etc., and has a molecular weight of 20,000-100,000.

7. The low-carbon high-density shotcrete elasticity reducing agent according to claim 3, characterized in that: In step S1, the entire process of synchronously adding solutions A and B is 2 to 4 hours.

8. The low-carbon high-density shotcrete elasticity reducing agent according to claim 3, characterized in that: In step S3, the drying temperature is 95-105° C. and the drying time is 3-5 hours.

9. A method for preparing a low-carbon high-density shotcrete elasticity reducing agent as claimed in any one of claims 1 to 8, characterized in that: The rheological component, the viscosity increasing component, the early strength component and the setting regulating component are mixed to obtain a elasticity reducing agent for low-carbon and high-density shotcrete.

10. An application of the low-carbon high-density shotcrete elasticity reducing agent as claimed in any one of claims 1 to 8, characterized in that: The elasticity reducing agent is added in an amount that replaces 5% to 10% of cement in concrete.

Citation Information

Patent Citations

  • Multi-component composite synergist for shotcrete and preparation method of multi-component composite synergist

    CN111574103A

  • Wet-process sprayed ultra-high performance concrete rheological property regulator and using method thereof

    CN111620591A

  • Nanometer springback inhibitor, preparation method thereof and application of nanometer springback inhibitor in sprayed concrete

    CN116768524A

  • Water-resistant rebound inhibition tackifier, and preparation and use methods and application thereof

    CN117567068A

  • Tunnel engineering sprayed concrete resilience reducing agent and preparation method thereof

    CN118084387A

Cited By

  • Elasticity reducing agent for early-strength impervious sprayed concrete in water-rich area as well as preparation method and application of elasticity reducing agent

    CN120192113A

  • Early-strength water-reducing agent for water-rich area early-strength anti-permeability shotcrete, and preparation method and application thereof

    CN120192113B

  • Sprayed concrete elasticity reducer and preparation method thereof

    CN121850435A